Assessing buildings’ adaptability at early design stages - Andrade, Joana Bonifácio (2019)
Buildings should be able to change and be adaptable according to newer requirements; otherwise, premature demolition can occur. The adaptability or lack of it in buildings affects the environment, society, and economy. If existing buildings are better-taken care of and re-used, their life expectancy extends, and fewer resources are used. Flexible and adaptable buildings enable not just recycling and reusing existing buildings, they allow upcycle of these buildings into urban regeneration projects. Additionally, buildings? early design phases are critical for their sustainability. If adequate measures are taken at these stages, sustainability concerns are overcome in a much easier, faster, economical, and efficient way. This paper describes the importance of addressing sustainable criteria during early design, with special attention to adaptability criteria. Based on the concept of open building and aiming to promote ease of dismantling and adjustability, the evaluation proposed comprises two sub-indicators: flexibility provision and (ii) adaptability capacity. The first accounts for design strategies to accommodate change, through the transformation capacity. The second aims to quantify the availability of space to be changed and adapted according to the occupiers? needs, following the open building concept by accounting the built area available to be transformed. By considering these aspects at the early design, it is possible to obtain buildings that live longer with lower environmental impact. Higher transformation ability means buildings can easier accommodate new requirements; greater disassembly potential can be achieved enabling replacement, reuse or recycling for the buildings? materials and components, thus promoting buildings? sustainability and resilience.